Negara Kesejahteraan (Welfare State) dalam Perspektif Pancasila - Putra, Marsudi Dedi (Jurnal Likhitaprajna, 2021)
Advancing the general welfare is the goal of the state as well as the mandate of the constitution. Welfare not only ensures a fair and equitable distribution of wealth; it also reduces poverty and provides basic services and provides social protection for every citizen. However, this noble goal has not been realized optimally. This research is normative legal research, and analyzed juridically and described descriptively. The results of the research on the principle of equitable welfare efficiency need to be supported by the state, civil society, and the market running in harmony. The welfare state that Indonesia wants based on Pancasila in the context of realizing social justice for all Indonesian people who have the spirit of divinity, civility, kinship and democratic mutual cooperation.